(untitled) (Global Conference on Medical and Health Sciences, 2026)
The use of analytical actions in the process of auditing the balance sheet allows the auditor to evaluate financial indicators by examining the probable relationship between them. This, in turn, makes it possible to assess the effectiveness of the planning methods used by the organization, to determine the existing consolidation, the scope of possible risk, bankruptcy, and so on. An example of simple quantitative analytical actions in the process of balance sheet audit is the analysis of financial activities based on simple coefficients. Advanced operations include trend analysis, analysis of variation, regression analysis, and modeling. The advantages of more complex analytical operationsare higher accuracy and objectivity, but their application is laborious and expensive, as a result of which analytical actions data are rarely used. However, at present, a large number of programs have been developed that allow simplifying the process of mathematical processing of large amounts of data (Table).